ASSESSMENT OF A SIMPLE FUNCTION TO EVALUATE THE RELATIONSHIP BETWEEN MASS FLUX REDUCTION AND MASS REMOVAL FOR ORGANIC-LIQUID CONTAMINANTED SOURCE ZONES - DiFilippo, Erica L. (2011)
The efficacy of a simple mass-removal function for characterizing mass-flux-reduction/mass-removal behavior for organic-liquid contaminated source zones was evaluated using data obtained from a series of flow-cell experiments. The standard function, which employs a constant exponent, could not adequately reproduce the non-singular (multi-step) behavior exhibited by the measured data. Allowing the exponent to change as a function of mass removal (as the organic-liquid distribution and relative permeability change) produced non-singular relationships similar to those exhibited by the measured data. Four methods were developed to characterize the variability of the exponent through correlation to measurable system parameters. Key factors that mediate the magnitude of mass flux (dilution and source accessibility) were accounted for using measures of source zone cross-sectional area, ganglia-to-pool (GTP) ratio, and relative permeability. The two methods that incorporated only the ganglia-to-pool ratio produced adequate simulations of the observed behavior for early stages of mass removal, but not for later stages. The method that incorporated parameters accounting for the source zone cross-sectional area (i.e., measure of system dilution) and source accessibility (GTP ratio and relative permeability) provided the most representative simulations of the observed data.